Stability, Existence and Uniqueness of Boundary Value Problems for a Coupled System of Fractional Differential Equations - Mahmudov, Nazim I.; Al-Khateeb, Areen (Mdpi, 2019)
The current article studies a coupled system of fractional differential equations with boundary conditions and proves the existence and uniqueness of solutions by applying Leray-Schauder's alternative and contraction mapping principle. Furthermore, the Hyers-Ulam stability of solutions is discussed and sufficient conditions for the stability are developed. Obtained results are supported by examples and illustrated in the last section.
Keywords: fractional derivative; fixed point theorem; fractional differential equation